2013
DOI: 10.1515/libri-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Competencies: A Multi-Country Examination of Reference Service Competencies

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Personal competencies such as interpersonal relations, library experience, and knowledge of a foreign language received the highest number of occurrences in the job ads, while library directors emphasized skills related to the organization of information such as cataloging and classification, as well as computer skills and information searching skills; course descriptions focused mainly on technological skills such as network management and information skills. The finding from the course description sample concurs with Saunders et al's (2013) multi-country study that found that searching skills are considered the most important for the 13 countries that participated in the study, followed by knowledge of online sources and databases. Similarly, in this study both of these skills were revealed to be among the most salient when analyzing each of the three samples.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Personal competencies such as interpersonal relations, library experience, and knowledge of a foreign language received the highest number of occurrences in the job ads, while library directors emphasized skills related to the organization of information such as cataloging and classification, as well as computer skills and information searching skills; course descriptions focused mainly on technological skills such as network management and information skills. The finding from the course description sample concurs with Saunders et al's (2013) multi-country study that found that searching skills are considered the most important for the 13 countries that participated in the study, followed by knowledge of online sources and databases. Similarly, in this study both of these skills were revealed to be among the most salient when analyzing each of the three samples.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, the technological skill cluster received the highest number of occurrences in the course descriptions while the number of occurrences in the job advertisements (fourth place) and the survey responses (third place) was rather low. In other words, as a result of the increase in the technological resources observed over the past two decades, LIS departments in Israel have designed study programs that prepare students to work in highly technological environments; however, as other studies have revealed, the demand for these skills in job ads have declined over the years (Choi & Rasmussen, 2009;Kennan et al, 2006;Saunders et al, 2013). For instance, Gottfried (2013) investigated whether an increased demand for technological knowledge and proficiency exists in job expectations, and found that technological skills such as web development and the ability to write HTML have declined consistently over the years.…”
Section: Discussionmentioning
confidence: 99%
“…(LIBER, 2013) Many other studies have been conducted on library competencies but seldom do they compare competencies across countries or outside traditional boundaries. An exception to this is a recent survey of reference service competencies with over 2400 respondents across 13 countries (Saunders et al, 2013). The results of this study highlight some important similarities and differences that 'could help reference librarians to manage and meet the expectations of their international patrons' (Saunders et al, 2013: 34).…”
Section: Internationalization Of Academic Libraries and The Increase mentioning
confidence: 65%
“…Research (Wagner, 2000) in Australia consisted of a series of focus groups which determined the following eight themes were critical: technology, communication, teamwork, user focus, business savvy, evidence-based practice, learning and education, and personal traits. In a multicultural examination of LIS skills and competencies in 13 countries, Saunders et al (2013) identified cultural variations in how librarians relate to patrons and patrons’ understanding of the librarian’s role, but found considerable consistency of the kind of skills required. In all the countries that participated in the study, searching skills were considered the most important along with knowledge of information sources, verbal communications, and listening.…”
Section: Literature Reviewmentioning
confidence: 99%